Equity and spatial accessibility of healthcare resources in online health community network - Gu, Hong; Cai, Yu-Feng; Sun, Kun; Zhao, Tian-Fang (Frontiers in Physics, 2024)
With the advent of digitized healthcare, Online Health Communities (OHCs) have become pivotal platforms for delivering and accessing medical services. Taking "Good Doctor website" as a study case, this study investigated the geographical distribution and fractal characteristics of the medical service network in China. A hierarchical, binary network are built from the datasets collected from the platform. Results unveil the hierarchical nature of hospital distribution and the interconnectivity among healthcare institutions. Shandong Province as a central node within the national hospital network, and networks of secondary hospitals show significant self-similarity and scale-free properties. Additionally, the small-world and fractal characteristics shed light on the rapid dissemination of medical information and the robustness of the healthcare network. The results offer a novel perspective for understanding and optimizing the distribution of medical resources, and help improve the efficiency of healthcare services supply.